2013
DOI: 10.1091/mbc.e13-01-0057
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin–binding site for host cell receptor GPP130 reveals unexpected divergence in toxin-trafficking mechanisms

Abstract: Manganese is specifically effective against Shiga toxin (STx) and STx1. STx2 does not bind the manganese-sensitive host cell receptor GPP130, because a histidine/asparagine pair that constitutes the binding site for GPP130 is not conserved. This reveals an unexpected and significant functional divergence in Shiga toxin evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…The structural profiles and spatial orientations of the β4–β5 loops appear nearly identical (Figure A). However, STx2B does not bind GPP130, and this lack of binding has been ascribed to a lack of conserved residues in the β4–β5 loop (Figure B). In STx1B, residues H 78 and N 79 in the β4–β5 loop are required for GPP130 binding and endosome‐to‐Golgi transport , but the corresponding residues in STx2B are E 76 and S 77 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The structural profiles and spatial orientations of the β4–β5 loops appear nearly identical (Figure A). However, STx2B does not bind GPP130, and this lack of binding has been ascribed to a lack of conserved residues in the β4–β5 loop (Figure B). In STx1B, residues H 78 and N 79 in the β4–β5 loop are required for GPP130 binding and endosome‐to‐Golgi transport , but the corresponding residues in STx2B are E 76 and S 77 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Hope that manganese could be used as a treatment for STEC infection diminished, however, when Gaston et al and additional work by Mukhopadhyay et al showed that the protective effects of manganese did not extend to Stx2 [65,66]. Gaston and colleagues also showed that manganese was more toxic, both in cultured cells and in mice, than was reported by Mukhopadhyay and Linstedt.…”
Section: Discussionmentioning
confidence: 99%
“…While ␤-lactamase confers antibiotic resistance, Shiga toxin 2 subunit B and the serine protease autotransporters are important for E. coli O104:H4 virulence. Subunit B of Shiga toxin 2 allows holotoxin surface attachment and retrograde transport into host cells (39). The O104:H4 AAF/1 major fimbrial subunit and a fimbrial chaperone protein, FimC, were also abundant in the growth medium.…”
Section: Detection Of Proteins From Minimal Mediummentioning
confidence: 99%